RETRACTED: Analysis of the thermally stressed state of the heat-generating element in the form of an ellipsoid - Kanareykin Alexandr (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001